Assessing Global and Local Radiative Feedbacks Based on AGCM Simulations for 1980–2014/2017. Issue 12 (19th June 2020) - Zhang, Rudong; Wang, Hailong; Fu, Qiang; Rasch, Philip J.
Abstract: We examine radiative feedbacks based on short‐term climate variability by analyzing atmospheric general circulation model (AGCM) simulations, including Atmospheric Model Intercomparison Project within CMIP phase 6 (AMIP6) with known effective radiative forcing (ERF) for 1980–2014 and one with zero ERF for 1980–2017. We first verify the Kernel‐Gregory feedback calculation by showing that both clear‐sky radiative fluxes and all‐sky radiative feedbacks from the kernel method agree with model simulations. We find that global‐mean net feedback for 1980–2017/2014 is −2 W m −2 K −1, about twice the feedback estimated for long‐term warming (4 × CO2 ) experiments. This difference is mainly caused by a near‐zero global‐mean net cloud feedback for 1980–2017/2014. We show that the lapse rate feedback for 1980–2017/2014 is the largest contributor to the amplified temperature change over the three poles (Arctic, Antarctic, and Tibetan Plateau), followed by surface albedo feedback and Planck feedback deviation from its global mean. Except for a higher surface albedo feedback in Antarctic, other feedbacks are similar between Arctic and Antarctic. Plain Language Summary: The global annual mean temperature at the Earth's surface has risen rapidly in recent decades. Three regions (Arctic, Antarctic, and Tibetan Plateau) of the Earth, called the "three poles", have warmed more than the global mean, a phenomenon commonly known as polar amplification. The global warming and polar amplification are a consequence of historical external forcings (due to changes in greenhouse gases, aerosols, ozone, solar radiation, volcanic eruptions, and land use) and feedback processes that influence the planet's response. Because of a short measurement record (since 1980) and natural variability, it is difficult to rigorously quantify how individual feedbacks explain polar amplification. Here, we use simulations without external forcing changes but with observed sea surface temperature (SST) changes for 1980–2017 and newly available simulations from many models with prescribed SSTs to verify a "kernel method" to estimate radiative fluxes and feedbacks. We then investigate the global feedback and local feedback over the three poles. We found that models indicate a stronger negative global‐mean net feedback for 1980–2017 than will occur over longer time periods when warming will be stronger. This is primarily due to a near‐zero global mean net cloud feedback estimated for the recent past. Key Points: The global net feedback for 1980–2017/2014 is estimated to be negative and stronger than that from long‐term warming (e.g., 4×CO2 ) experiments The stronger negative net feedback is primarily due to a near‐zero global‐mean cloud feedback for 1980–2017/2014 Lapse rate feedback is the largest contributor to the amplified temperature response seen over the three poles relative to the tropics for 1980–2017/2014